VULNERABILITY ASSESSMENT OF MULTI-STOREY BUILDINGS IN PRODIA HEALTH CLINIC BUILDING IN PADANG USING RAYLEIGH WAVE. - Khumairah, Resti; Putra, Rusnardi Rahmat (Teknik Sipil Universitas Negeri Padang, 2023)
Vulnerability assessment of the building has been conducted at the Prodia Health Clinic building in Padang city. Microtremor data was used, and the main data from this research comprised seismic wave data processed through a series of software such as GPL, Cygwin, Bido 2.02, and Geopsy. This processing yielded the natural frequency values of the building structure under investigation. The research method involved the use of the FSR (Floor Spectral Ratio) method to estimate various transfer function parameters (such as amplification, natural frequency, and vulnerability index) and the RDM (Random Decrement Method) method to characterize the dynamic properties of the building (such as damping ratio and natural frequency). The results of the research indicated a strong relationship between the FSR and RDM methods, producing accurate damping ratios through the validation of the natural frequencies obtained from both methods. In the context of the research findings, the natural frequency values obtained were 2.92 – 3.80 Hz for the FSR method and 4.01 – 4.24 Hz for the RDM method. Using the HVSR method, the natural frequency of the ground yielded a value of 0.399392 Hz and an Amplification (Ao) of 0.50324. Concerning the vulnerability of the ground, it was found that the area around the Prodia Health Clinic building in Padang city tends to experience lower damage in the event of an earthquake. Based on the drift angle calculation, it can be concluded that the 4th floor of the Prodia Health Clinic building in Padang city, in the x-direction, has a higher risk of damage compared to other floors when responding to earthquake vibrations with seismic motion (α) of 398 gal and 450 gal.